Satisfaction and loyalty in B2B relationships in the freight forwarding industry: adding perceived value and service quality into equation - Gil-Saura, Irene; Berenguer-Contri, Gloria; Ruiz-Molina, Eugenia (Transport, 2018)
This paper focuses on analysing the determinants of satisfaction (service quality, perceived value), as well as its possible influence on customer loyalty of freight forwarders to freight transport service providers (by road/maritime/air) in Spain. To this end, we propose a causal model tested using information from 205 freight forwarders collected through personal interviews. The model was estimated using the Partial Least Squares (PLS) approach. Moreover, the existence of differences in the perceptions on the analysed variables between transport modes is tested through ANOVA. Results show that service quality has an influence on customer satisfaction, both directly, as well as through perceived value. In turn, it is confirmed the relationship between satisfaction with the transportation company and customer loyalty. Furthermore, there are significant differences in quality dimensions and satisfaction between transport modes. This study confirms the importance of service quality and perceived value to promote the link between chain actors: freight forwarder and transport service provider. The main aim of this research is to go deeper into the study of satisfaction and loyalty of freight forwarders to freight transport service providers. Findings provide evidence about differences in the dimensionality of service quality between B2C and B2B settings and, even in the latter, differences between freight forwarding services and other industries are observed. The present paper is one of the few studies that obtains relevant information about several transport modes simultaneously and the findings reinforce the notion that perceptive processes in each of them are different.